PENERAPAN SAK ETAP DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UMKM KING BATAKO JAYA - B51112021, Roberto Luis (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
King Enterprises brick Jaya is a Micro, Small and Medium Enterprises selling brick. Financial Statements recorded by very simple brick Enterprises notes out of money and the income statement that are not routinely made every month. Business Owners brick still not implementing SAK ETAP. The purpose of this study is the researchers wanted to know SAK ETAP implementation on King Enterprises brick Jaya and obstacles that make the effort brick Jaya King could not prepare financial statements. Based on the existing problems, researchers devise Financial Statements in the form of Income Statement, Statement of changes in capital, balance sheet and cash flow statement. This is to assist businesses in understanding the financial statements based on the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) in particular manager brick Jaya King Enterprises. In this study, researchers used qualitative research methods descriptive. Descriptive research focuses on the explanation of the facts obtained sistemasis time of the study. Ie analyzing existing data and conduct an interview with Business Owners brick to get good information and correct. Keywords: SAK ETAP, Preparation of Financial Statements, SMEs